PROMOTING ENGAGE STUDY ACTIVATE (ESA) TECHNIQUE TO TEACH SPEAKING SKILL - G Gunadi; Fitri Novia; Rekha Asmara (Universitas Tridinanti Palembang, 2021)
ESA (Engage, Study, Activate) technique is one of alternative ways to teach EFL students how to speak in English, comprising three steps: engage, study, and activate. It is believed that this technique can assist the teachers in arousing students' interest, curiosity, and emotion, as well as encouraging them to orally express their feelings, information, and language. The goal of the research was to see whether there was a significant difference in speaking performance between the students who learned using ESA technique and those who were not. A quasi experimental research was administered as the design of the research. The sample was taken by using purposive sampling technique. The researchers considered the number of the students and whether the sample was taught by the same English teacher as choosing the sample. The data was collected using an oral test. The data was analyzed using the t-test. Based on the result of independent sample t-test, it was found that tobtained was 3.174. It was higher than ttable (1.999). It indicated that H0 was rejected and Ha was accepted. Therefore, it confirmed that the students who were taught using ESA technique had better speaking achievement than the students who were not taught using ESA technique. Keywords: Engage study activate technique, speaking, recount text